A New Enantiornithine (Aves) Preserved in Mid-Cretaceous Burmese Amber Contributes to Growing Diversity of Cretaceous Plumage Patterns - Xing, Lida; O’Connor, Jingmai K.; Niu, Kecheng; Cockx, Pierre; Mai, Huijuan; McKellar, Ryan C. (Frontiers in Earth Science, 2020)
Recent discoveries of enantiornithine birds trapped in amber have increased the lower size limit of members of this clade, increased their morphological diversity, and provided significant new data regarding their plumage. Here we describe a new specimen that consists of the distal extremities of both forelimbs and hindlimbs. Size and morphology suggest the specimen represents an immature individual. Although the skeletal morphology is poorly preserved, the new specimen most probably represents a member of the Enantiornithes based on the sum of its preserved morphologies, including its small size, elongate penultimate pedal phalanges, and large recurved unguals. Based on the lengths of the metatarsals, the new specimen is even smaller than previously described enantiornithines that preserve these elements; however, the forelimb elements are longer than those in the only other specimen preserving comparable overlapping skeletal material. This is suggestive of a diversity of limb proportions in the Burmese enantiornithine fauna, similar to that observed in the Jehol avifauna, in which intermembral indices range from approximately 1 to 1.5. The wing appears to consist of eight primaries, less than that of neornithines, contributing to mounting data that suggests the flight apparatus of enantiornithines was unique from that of other basal birds and neornithines. The well-preserved flight feathers are ornamented with pale basal bands, further adding to the diversity of Cretaceous plumage patterns revealed by Burmese amber specimens.